PRINSIP CHECKS AND BALANCES DITINJAU DARI SISI DAN PRAKTIK - FAHARUDIN FAHARUDIN (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
The purpose of this research is to get a full description about the parliament concept in Indonesia that no clear enough use Threecameralism system (MPR, DPR, DPD) Bicameralism (DPR and DPD), or Unycameralism (MPR). Similarly, if use Bicameralism form (DPR and DPD) so is not make check and balances of character between DPR and DPD make Bicameralism concept in Indonesian only Weak Bicameralism not Strong Bicameralism. Result of this research is power phenomenal more arbitrarily that’s why the power must be limited and restriction of the power must be regulated and limited in certainty of legislation or constitution that purpose no happen accumulation power to one branch of power. Trias Politica doctrine divide three branch of power that is Legislative as make the rule, executive to ride of it, and Judicative to investigate that follow with checks and balances mechanism, so that it’s impress the arbitrarily or maybe make escaped from arbitrarily.